Synthesis of polyynes to model the sp-carbon allotrope carbyne - Chalifoux, Wesley A.; Tykwinski, Rik (Nature Chemistry, 2010)
Carbyne is an allotrope of carbon composed of sp-hybridized carbon atoms. Although its formation in the laboratory is suggested, no well-defined sample is described. Interest in carbyne and its potential properties remains intense because of, at least in part, technological breakthroughs offered by other carbon allotropes, such as fullerenes, carbon nanotubes and graphene. Here, we describe the synthesis of a series of conjugated polyynes as models for carbyne. The longest of the series consists of 44 contiguous acetylenic carbons, and it maintains a framework clearly composed of alternating single and triple bonds. Spectroscopic analyses for these polyynes reveal a distinct trend towards a finite gap between the highest occupied molecular orbital and the lowest unoccupied molecular orbital for carbyne, which is estimated to be ∼485 nm (∼2.56 eV). Even the longest members of this series of polyynes are not particularly sensitive to light, moisture or oxygen, and they can be handled and characterized under normal laboratory conditions. © 2010 Macmillan Publishers Limited.